Navigation-driven handoff minimization in wireless networks. (October 2016) - Zhao, Yanchao; Li, Wenzhong; Lu, Sanglu
Abstract: Interactive wireless Internet applications (e.g. VoIP over wireless networks, realtime monitoring and some mobile-cloud offloading applications) desire high-quality links and smooth connectivity during movement. In order to support seamless roaming in wireless networks, handoff optimization constantly attracted a lot of attentions. Most existing approaches aim at reducing handoff latency by modifying the communication and association protocols. While these methods provide significant savings in handoff latency, frequent handoffs could still be crucial and problematic for interactive applications. In this paper, we propose a new method for handoff optimization by introducing navigation to minimize the handoff frequency. We first formulate the navigation-driven handoff minimization problem in general case, then propose an optimal algorithm to the scenario of global knowledge, a heuristic localized algorithm for scenario of local knowledge, and a measurement-based algorithm for scenario of real communication settings. Implementation issues of the proposed algorithms are discussed and simulations based on real world AP deployment are used to evaluate their performance. Experiment results show that our algorithms reduce handoff frequency by 23% in average, compared to existing strategies. Extensive experiments of the impact of the high-layer QoS performance are also conducted to prove the effectiveness of our work.